Implementation management : high-speed strategy implementation - Kolbusa, Matthias (Berlin : Springer, 2013)
Current technological, demographic and globalization trends are not only leading to intensified competition; they also indicate that new business models are rapidly emerging, but only to disappear again just as quickly. Timely recognition of the new changes, jettisoning of old approaches, and rapid implementation of the currently required changes within a company are now decisive competitive factors. Those who best survive (and thrive) in the future will be those who dramatically increase their success rate within this change process. Building on his best-selling book'The Strategy Scout' Matthias Kolbusa explains the decisive principles in this rapidly changing business environment.
The Difference Between Goal, Strategy, Tactics and Execution -- The Implementation Dilemma -- The Quintessence of Implementation Success Concept Development -- Method Cancer Diagnosis, Elimination and Avoidance -- How Not to Be Confused Mastering Complexity -- The Million Dollar Question What About Integration? -- Staying on the Ball Consistency Instead of Severity -- Moving Up a Gear Implementation Gravitation and Implementation Excellence -- Overview Quick Steps to Accelerate Implementation -- Appendix.
Includes bibliographical references and index.
Keywords: Organizational change; Strategic planning